Déjala morir - Romero, Yurieth; Telecaribe (Television network) (Santa Marta, Colombia : Editorial Unimagdalena, 2019)
This book is based on the 2017 miniseries of the same title, broadcasted by TeleCaribe. It tells the story of Afrocolombian singer Juana Emilia Herrera, known as "la niña Emilia."
Online resource; title from PDF title page (Digitalia, viewed November 7, 2019)
Keywords: Herrera, Juana Emilia, -- 1932-1993.; Déjala morir (Television program); Folk singers -- Colombia -- Biography; Singers -- Colombia -- Biography; Bullerengue (Music); Biographies; Biographical television programs; Television mini-series.; Electronic books